How Smartphones Transformed Market and Competition of Mobile Broadband in OECD Member Countries - Sobee Shinohara; Hiroyuki Morikawa; Masatsugu Tsuji (International Telecommunications Society (ITS), 2016)
Smartphones such as iPhones and Android was introduced to the market around 2007-9 in various OECD member countries. Since then, the transformation of the market was observed, which include (i) rapid growth of mobile broadband (3G+4G); (ii) severer market competition; and (iii) upheaval of market share of mobile carriers. More concretely, 34 OECD countries show the following: (i) the average diffusion rate of mobile broadband in 2008 was about 40%, whereas in 2012 it increased up to 80%; (ii) HHI also reduced in all countries; and (iii) it is common to countries that the carriers which introduced iPhones raised their market shares, whereas those which did not introduce lowered shares. This paper examines the above three transformations in 34 OECD countries by panel data analysis from 2000 to 2012 to identify factors of rapid growth of mobile broadband and market competition. In so doing, the paper estimates the mobile broadband adoption ratio by the following variables: monthly charge of voice services; monthly Data rate; download speed; HHI; GDP per capita; FTTH adoption ratio; the launches of Androids and iPhones; and other policy variables such as Frequency auction and MNP. By using the instrumental variables method, the results obtained are summarized as follows: (1) Price (Voice) is negatively significant; (2) Price (Data)/Speed is not significant; (3) Income is positively significant; (4) HHI is negatively significant; and the followings are positively significant; (5) FTTH adoption ratio; and (6) Launches of smartphones. The results of the analysis also use for discussing the above transformations such as (ii) and (iii).
Keywords: 330; Mobile broadband; Panel data analysis; Smartphone; iPhone; Android; Backhaul